Characterization of Metal Nanoparticles/Polyurethane Foams for Practical Applications - Toma Fistos; Roxana Ioana Matei (Brazdis); Anda Maria Baroi; Irina Fierascu; Radu Claudiu Fierascu; Raluca Augusta Gabor; Marius Eduard Lungulescu; Nicoleta Nicula; Miruna Stan (Proceedings, 2023)
Polyurethane foam can generally be defined as an expanded cellular product produced by the interaction of active compounds with hydrogen, water and isocyanates [...]